Application of The Phonic Method to Improve The Early Reading Skills of Mentally Retarded Children: Penerapan Metode Fonik Untuk Meningkatkan Kemampuan Membaca Permulaan Anak Tunagrahita - Khurota A'yun; Kemil Wachidah (Academia Open, 2022)
This study has the aim of conducting research, namely to determine the improvement of reading skills for mentally retarded children by applying a reading method, namely the phonic method. The phonic method for mentally retarded students starts from hearing the sounds of letters and letter shapes, combining letters by letter into syllables, to reading nouns. This study uses a descriptive quantitative approach with the type of experimental research. And this study uses an A-B-A research design with 4 subjects with mental retardation, carried out in the Baseline A phase carried out in 2 sessions, in the Intervention phase 6 sessions, and in the Baseline A phase 2 sessions. The results of this study can be seen from the progress in each session that has been carried out, the progress of the subject's reading ability, and the progress of the conditions raised by the research subject in each session. And the results of the 4 research subjects showed that there was an increase in early reading skills for mentally retarded children by applying the phonic method.